Analisis Efisiensi Pengendalian Biaya Kualitas Pada Sweet Roti Moderen Samarinda - AdisAdisthy Shabrina Nurqamarani3, Heriyansyah Titin Ruliana 2, (EKONOMIA, 2020)
This study aims to determine and analyze the efficiency of quality control costs at Sweet Roti Moderen SamarindaÂ in 2017 and the efficiency of quality control costs at Sweet Roti Moderen Samarinda in 2018.The basic theory used in this study is Cost Accounting and Management Accounting which focuses on controlling the quality costs of a product. The analytical tool used is a quality cost control report.The results showed that the quality cost control at Sweet Roti Moderen Samarinda in 2017 it had not been done efficiently and the quality cost control at the 2018 Sweet Roti Moderen Samarinda it had not been done efficiently.Further suggestions for Sweet Roti Moderen Samarinda in determining quality control costs should record each cost incurred in their financial statements. The cost of quality control comes from other costs, which from interviews with managers and accounting staff only estimate these costs without a definite record. All fees and transactions must be recorded to obtain accurate financial information.